Computerized simulation system for ECM radar system - Salleh, Mohamad Sabri (2007)
The purpose of this project is to develop a simulation system for Electronic Counter Measure (ECM) Radar System. The study of ECM system consist of basic principle of radar, jammer, ECM and Electronic Counter Counter Measure (ECCM). The principle of electromagnetic spectrum is the basic background for all calculation and simulation. It is user friendly for design and training purposes. The simulation system provides the application for user to design and learn about ECM Radar System. User will be able to appreciate the principle behind the operation of Electronic Warfare (EW). This thesis documents the development of computerized simulation system by using principle of software engineering which is Object Oriented (OO) Methodology. The process started with requirement analysis on how the users wish the system to be. The user needs a system which is able to evaluate equipment and train personnel about EW theory. Then Unified Modeling Language (UML) was used as a tool to implement the OO methodology. Use case diagram were used, based on the requirement analysis. From the use case diagram, use case scenarios are created to view on how the system works. Next sequence diagrams were used to view the internal process within the simulation system. Finally before code generation, the flow chart of the simulation algorithm was used. The system is based on C++ Builder application; it has the capability of OO programming with the enhancement of Visual Component Library (VCL). OO methodology with the tools of UML has aided in the development of the system in a well structured manner.